Queensland immigrants Port of Maryborough 1861-1901 - Johnson, Eileen B.; Gould Genealogy & History ([Modbury, S. Aust.] : Gould Genealogy & History, 2010)
"Maryborough Immigrants" contains details on 20,735 immigrants who arrived at the port of Maryborough in Queensland between 1861 and 1901. "Passengers & Crew" contains details on 6,620 immigrants who arrived in Queensland in 1862 - both passengers and crew. Both indexes were compiled by Eileen Johnson.
Maryborough Immigrants -- Passengers & Crew.
CD-ROM.
Title from container.
"PRO061 Gould Genealogy" -- Sticker on container.
Electronic version of print publication.
System requirements: This CD-ROM utilises the QFHSdatasearch, developed using Microsoft Visual Basic Version 6 to enable access to a Microsoft Access database, using the DAO (Data Access Objects) library. Selfcontained, no additional software is required.
Digital content preserved
Keywords: Ships -- Queensland -- Maryborough -- Passenger lists -- Indexes; Passenger ships -- Queensland -- History; Immigrants -- Queensland -- Maryborough -- History; Maryborough (Qld.) -- Emigration and immigration -- History; Maryborough (Qld.) -- Genealogy -- Indexes; Queensland -- Emigration and immigration